Manfaat Latihan Jalan Kaki Terhadap Peningkatan Derajat Kesegaran Jasmani Usia Lanjut (Lembaga Penerbitan Universitas Esa Unggul, 2007)
Objectives: The amounts and percentage of older age who are more than 60 years old in Indonesia from year to year are increasing. As comparation in 1990 the amounts were 7.99 millions percentage 5.55 % of total resident : in 2000 the amounts were 15.88 millions percentage 7.60 % of total resident. Aging is a physiology and pathophysio-logy process in the human body which run continuosly and can’t be stopped. We can make some effort to minimize the aging process so the general condition is getting better and the life span will be prolonged. According to Katz VL in 1991 it was that one of the effects is to increase the general condition by increasing the physical fitness Physical fitness is personal activity to do daily physical activity, without causing exhaust feel. Method: We have a program of health education and walking exercise program one mile or 1.6 km. The exercise frequency is 3 times a week, and is done for 3 months. One’s physicall fitness can be measured by VO2 maximal (maximal oxigen consumption para-meter). The reason of using walking exercise as a tool to measure VO2 is that in this exercise most of the muscles are in active motion, so it will increase the action pump of perifer blood vessels. Venous return and stroke volume will increase so that VO2 maxi-mal is increasing. Results: From 30 samples of study it’s found that average of VO2 ma-ximal amounts before walking exercise : 25.89 in l/kg/minute, and after walking exercise the average of VO2 maximal 31.65 in l/kg/minute. The research has been done in Mandala Krida Stadion. The objects of the study are members of Paguyuban Pejalan Kaki Mandala Krida. Keywords: Physical Fitness, Walking Exercise, Active Motion